The Effect of Leadership, Compensation, and Organizational Culture on Organizational Commitment and Job Satisfaction Employees of PT Meranti Nusa Bahari Balikpapan - Didik Hadiyatno (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the significant influence of the variables of leadership, compensation and organizational culture on organizational commitment and job satisfaction of employees of PT Meranti Nusa Bahari Balikpapan. The population in this study were all employees of PT Meranti Nusa Bahari Balikpapan as many as 87 people and the number of samples was the same as the population of 87 people. The data collection used is by distributing questionnaires to respondents who are at PT Meranti Nusa Bahari Balikpapan. With Smart PLS software. (Partial Least Square) The results of the analysis showthat leadership and compensation have a positive and significant effect on organizational commitment, organizational culture has a positive and insignificant effect on organizational commitment and job satisfaction, leadership and compensation have a positive and insignificant effect on job satisfaction, and organizational commitment has a positive and significant effect on job satisfaction.